Plan Colombia and security dynamics between Ecuador and Colombia - Cadena Gómez, Juan Pablo (2011)
This article analyzes the reasons for the increasing levels of instability in the relations between Ecuador and Colombia during the first years of the current century, by describing processes of increased security concerns that occurred within both countries and their bilateral relations. The fact that domestic and international security had occupied prominent space on the bilateral agenda has favored that the two countries’s overall international relations turned out to be instable. On a similar note, this hypothesis is examined through an analytical description of the processes that had led to a suspension of all foreign relations between Ecuador and Colombia in 2008.